2001
DOI: 10.1523/jneurosci.21-12-04490.2001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Direction of Elemental Luminance Gradients on the Responses of V4 Cells to Textured Surfaces

Abstract: The texture of an object provides important cues for its recognition; however, little is known about the neural representation of texture. To investigate the representation of texture in the visual cortex, we recorded single-cell activities in area V4 of macaque monkeys. To distinguish the sensitivity of the cells to texture parameters such as density and element size from that to spatial frequency, we used texture stimuli mimicking shaded granular surfaces. We varied the size and density of the texture elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…Previous physiological studies have shown that neurons in V4 respond to various visual attributes (33) including shape (27,34), color (35,36), disparity (37,38), and texture (6,22). In particular, many studies have demonstrated that V4 neurons show I n t o le r a n t T o le r a n t Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous physiological studies have shown that neurons in V4 respond to various visual attributes (33) including shape (27,34), color (35,36), disparity (37,38), and texture (6,22). In particular, many studies have demonstrated that V4 neurons show I n t o le r a n t T o le r a n t Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Their algorithm is particularly inspiring because PS statistics use filters and computations that share biological properties. It was recently shown, for example, that a version of their synthesis algorithm can generate perceptually indistinguishable visual images (visual metamers) (21) and that naturalistic textures incorporating these summary statistics strongly activate neurons in V2, compared with noise images lacking these features (7).Given the previous successes in the parametric description of textures, it is tempting to expect that promoting this framework will reveal a full picture of texture representation in the subsequent stages in the ventral pathway, such as area V4, where many neurons show selectivity for textures (6,22). However, such an attempt has been hampered by a fundamental difficulty of data sampling due to the high dimensionality of natural texture space.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that we use the terms "edge" and "line" detectors merely as conventional descriptive terms; it is now generally understood that these terms are misleading if interpreted literally. Thus, the formal operators may well have rather immediate neurophysiological correlates (Hanazawa & Komatsu, 2001).…”
Section: Theorymentioning
confidence: 99%
“…Area V4 receives input from V1/V2 and is known to comprise neurons selective for various aspects of visual information, such as shape [38], color [55] or texture [24]. In this paper we are concerned with shape and, therefore, we are mainly interested in the function of shape-selective V4 neurons.…”
Section: Introductionmentioning
confidence: 99%